Bagaimana Pengaturan Kepemilikan Cryptocurrency Oleh Perusahaan Berdasarkan Standar Akuntansi Keuangan? - Firmansyah, Amrie; Pamungkas, Unggul Dwi (Jurnal Ilmiah Akuntansi Kesatuan, 2021)
This study investigates the application and recognition of accounting policies for ownership of Cryptocurrency assets by companies in Indonesia based on Financial Accounting Standards. This study uses a qualitative method with a scoping review approach to map the literature related to the concept of cryptocurrency and accounting arrangements for cryptocurrency ownership by companies. The scoping review carried out several stages, namely problem identification, identifying literature sources, literature selection, mapping and collecting literature, and discussion analysis. This study concludes that ownership of cryptocurrency by companies can be classified as assets based on IFRS and PSAK. The most relevant type of asset classification for Cryptocurrencies is inventory or intangible assets, depending on the purpose of ownership of the company. This research indicates that with the significant increase in the use of cryptocurrencies, standard-setting bodies need to set clear and specific accounting standards to help reduce uncertainty and provide relevant and useful guidance to both preparers and users of financial statements.